Purification of Human SIRT4 in Escherichia coli. - Park, Albert. (Tufts Archival Research Center, 2017)
The sirtuins (SIRT1–7) comprise a conserved class of NAD-dependent enzymes involved in metabolic regulation and cell survival. Their dependence on NAD inherently renders the sirtuins sensors of energy and thus offers a mechanistic link among energy availability, metabolism, and cell survival. Of the mitochondrial sirtuins, SIRT4 is the least biochemically understood sirtuin. Although ADP-ribosyltransferase, deacetylase, and lipoamidase activities have been ascribed to SIRT4, functions for which SIRT4 has robust activity have yet to be identified. Efforts to purify and characterize SIRT4 have been hampered by SIRT4’s tendency to aggregate upon overexpression. Our aim was to develop an unbiased approach to identifying the mechanistic properties of SIRT4 by leveraging the canonical sirtuin deacylation reaction, and to optimize purification conditions to enrich the yield of soluble SIRT4 protein. We show that insulin-degrading enzyme is a potential binding partner of SIRT4 that enhances SIRT4’s solubility upon co-expression in E. coli.